Answer:
C. 10 times greater
Step-by-step explanation:
every time you move left a number space, the value increases by a multiple of 10x (the opposite is true for moving right)
for example:
1.0
10.0
100.0
<u>1</u><u>0</u><u> </u><u>is </u><u>1</u><u>0</u><u>x</u><u> </u><u>greater </u><u>than </u><u>1</u>
<u>1</u><u>0</u><u>0</u><u> </u><u>is </u><u>1</u><u>0</u><u>x</u><u> </u><u>greater </u><u>than </u><u>1</u><u>0</u><u> </u><u>or </u><u>1</u><u>0</u><u>0</u><u>x</u><u> </u><u>greater </u><u>than </u><u>1</u>
<u>*</u><u>notice </u><u>how </u><u>the </u><u>number </u><u>1</u><u> </u><u>is </u><u>moving </u><u>one </u><u>space </u><u>to </u><u>the </u><u>left</u>
I'll say the first integer is x. The next consecutive odd number would be x+2. If the sum of the odd integers is 236, the equation would be
x + (x + 2) = 236
solve for x
2x + 2 = 236
subtract 2 from each side of the equation
2x = 234
divide both sides by 2
x = 117
117 is the first odd integer. to find the other integer (x + 2), substitute 117 for x, and you have 117 + 2, which equals 119
The two consecutive odd integers that add up to 236 are 117 and 119.
Answer:
e=30
k=15/2
h=90
Step-by-step explanation:
3e=60
e=30
30+4k=60
4k=30
k=15/2
15/2+2h=30
2h=45/2
h=90
Answer:
x + 2, x ≠ -2
Step-by-step explanation:
Note that F(x) = x^2 + 4x + 4 factors into (x + 2)^2, and that we are dividing this by g(x) = x + 2. The quotient is x + 2, which in this problem has been named h(x).
The quotient (f/g)(x) is therefore x + 2 EXCEPT that this is not defined at x = -2, because the denominator, x + 2, will be zero there, undefined.
Answer:
D
Step-by-step explanation:
Because you have to do work